Mycophenolic Acid as Possible Corrosion Inhibitor in Chloride Medium. (31st January 2018) - Pérez Valdelamar, M. J; Espinoza-Vázquez, Araceli; Rodríguez-Gómez, Francisco Javier; Del Valle Perez, Paulina; Mata, R.
Abstract : Mycophenolic acid ((4E)-6-(4-hydroxy-6-methoxy-7-methyl-3-oxo-1, 3-dihydro-2-benzofuran-5-yl)-4-methyl-4-hexenoic acid) is extracted from the fungus Penicillium brevicompactum . In this research, the properties of mycophenolic acid for corrosion inhibition are tested in static conditions and turbulent flow by means of the Electrochemical Impedance Spectroscopy (EIS) technique. The efficiency results showed that the mycophenolic acid is effective in static conditions from low concentrations, remaining practically constant when the concentration of the compound is increased with ղ of 90 %.